Concrete Heat Treatment Methods (Czech Journal of Multidisciplinary Innovations, 2022)
The article presents the results of studies of the influence of ambient temperature on the modes of heat and moisture treatment of concrete. The method of assignment of modes of heat and moisture treatment of concrete, taking into account the temperature of the hot climate, is proposed.